2004
DOI: 10.1177/0013124504266827
|View full text |Cite
|
Sign up to set email alerts
|

African American Parents’ Educational Orientations

Abstract: Research on race, social class, and parent involvement in education often implies that parents' educational orientations result directly from their social class or racial group backgrounds. In this article, the authors study the involvement of working-class and middle-class African American parents. They argue that these parents' educational orientations are informed by the educational environments they navigate, their resources for negotiating these environments, and their prior social class and race-based ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…As shown in the Chicago school reform movement, schools improve when stakeholders work together toward a shared goal (Bryk & Schneider, 2002). In addition, the literature is replete with studies showing the importance of parental involvement in schools (Bryk & Schneider, 2002;Cutler, 2000;Diamond & Gomez, 2004;Lareau, 2003). This literature does not, however, sufficiently address either the inherent tension between parents and school or the ways in which many principals work with parents, seeking their engagement and support while limiting and controlling their involvement and influence.…”
Section: Discussion: "Managing" Parentsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in the Chicago school reform movement, schools improve when stakeholders work together toward a shared goal (Bryk & Schneider, 2002). In addition, the literature is replete with studies showing the importance of parental involvement in schools (Bryk & Schneider, 2002;Cutler, 2000;Diamond & Gomez, 2004;Lareau, 2003). This literature does not, however, sufficiently address either the inherent tension between parents and school or the ways in which many principals work with parents, seeking their engagement and support while limiting and controlling their involvement and influence.…”
Section: Discussion: "Managing" Parentsmentioning
confidence: 99%
“…More recent work has focused on the power dynamics that often underlie the capacity of schools to work with a variety of parents and the capacity of parents to connect with schools. This recent work has focused on the notions of cultural capital (Crozier, 2001;Lareau & Horvat, 1999), self-efficacy (Hoover-Dempsey & Sandler, 1997), social class (Lewis & Forman, 2002;Diamond & Gomez, 2004), and social networks (Sheldon, 2002) as researchers have grappled with the ways in which race and social class shape parents' interactions with schools and how power differentials affect the parent-school relationship. Some authors have connected parental involvement and leadership research, focusing on the degree to which authentic participation goes beyond traditional notions of school management involving stakeholders in a democratic process of power sharing (Anderson, 1998;Furman & Starratt, 2002).…”
Section: School Leadership and Parental Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents tend to choose schools with students who are racially/ethnically similar to their children (Garcia, 2008;Stein, 2015). Higher income and more educated parents, meanwhile, may be more likely to know about and utilize school choice options (Diamond & Gomez 2004;Holme, 2002). Beyond race and class, parents who are more involved in their children's formal education may be more likely to exercise choice (Teske & Schneider, 2001).…”
Section: School Choicementioning
confidence: 99%
“…This rift is not unique to Samoans (see, for example, Desimone, 1999; Empleo, 2006; Hill & Tyson, 2009; Irizarry, 2007; Jeynes, 2005; Tyler et al, 2008; Wallitt, 2008; Weihua et al, 2012), but it does illuminate the disconnect between teacher and parent communication and expectations for students (Epstein & Sheldon, 2002; Moll et al, 1992; Pena, 2000; Valdés, 1996). Research has shown that parental engagement does affect achievement (Hill & Tyson, 2009; Jeynes, 2005) and that educational orientations are often influenced by different perceptions of the home and school contexts (Diamond & Gomez, 2004; Green & Hoover-Dempsey, 2007; Ice & Hoover-Dempsey, 2011). It is also a multidimensional construct (LeFevre, & Shaw, 2012; Weihua et al, 2012) that needs to account for systemic barriers and institutional obstacles (Martinez-Cosio, 2010), school climate (E.…”
Section: Theoretical Framework: Understanding Cultural Assets Across mentioning
confidence: 99%